2020
DOI: 10.3390/su12198278
|View full text |Cite
|
Sign up to set email alerts
|

Communication on Sustainability in Spanish Universities: Analysis of Websites, Scientific Papers and Impact in Social Media

Abstract: This study analyses how Spanish universities are communicating their commitment to sustainability to society. That entailed analysing the content of their websites and their scientific papers in sustainability science and technologies and measuring the impact of such research in social media. Results obtained from bibliometric approaches and institutional document analysis attest to intensified interest in sustainability among Spanish universities in recent years. The findings revealed an increase in the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
1
10
0
1
Order By: Relevance
“…The corpus analysis indicates that discursive representations of sustainability are explicitly present on the University of Oxfordís webpages associated with the ELT programs. The presence of discursive representations of sustainability in the corpus is in line with the previous studies (Amey et al, 2020;Fernández-Vázquez 2021;Filippo et al, 2020;Hart et al, 2015;Joseph, Engkamat, & Tawie, 2013;Salvioni et al, 2017) which indicate that high-ranking universities tend to provide sustainability-related disclosures, statements, and other types of sustainability discourse on their websites. In this study, a range of discursive representations of sustainability has been identified on the Department for Continuing Education webpages at https://www.conted.ox.ac.uk/ (the University of Oxford, 2022b) and the Department of Education at http://www.education.ox.ac.uk/ (the University of Oxford, 2022c).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…The corpus analysis indicates that discursive representations of sustainability are explicitly present on the University of Oxfordís webpages associated with the ELT programs. The presence of discursive representations of sustainability in the corpus is in line with the previous studies (Amey et al, 2020;Fernández-Vázquez 2021;Filippo et al, 2020;Hart et al, 2015;Joseph, Engkamat, & Tawie, 2013;Salvioni et al, 2017) which indicate that high-ranking universities tend to provide sustainability-related disclosures, statements, and other types of sustainability discourse on their websites. In this study, a range of discursive representations of sustainability has been identified on the Department for Continuing Education webpages at https://www.conted.ox.ac.uk/ (the University of Oxford, 2022b) and the Department of Education at http://www.education.ox.ac.uk/ (the University of Oxford, 2022c).…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, the analysis of the corpus reveals no explicit discursive reference to the following university-wide sustainability goals: i) sustainable food, ii) sustainable international travel, and iii) carbon offsetting (see The University of Oxford, 2022a). The discrepancy between the discursive representations of sustainability that are found on the ELTrelated webpages and the sustainability goals that are described on the Sustainability webpage (The University of Oxford, 2022a) is evocative of the prior literature (Filippo et al, 2020;Hart et al, 2015), which indicates that while high-ranking universities promote sustainability on their official websites, it is not equally reflected on the disciplinespecific webpages. Moreover, the identified discrepancy between the present findings and the sustainability goals postulated by the University of Oxford on the universitywide level is exacerbated by the differences in discursive representations in the study and the prior research (Filippo et al, 2020, p. 14) that reports such discursive representations of sustainability as renewable energy, innovation and governance, quality education, health and well-being, sustainable consumption, zero hunger, and climate action.…”
Section: Discussing Rq1mentioning
confidence: 98%
See 3 more Smart Citations